Digital image analysis agrees with visual estimates of adult bone marrow trephine biopsy cellularity. (9th December 2017) - Hagiya, A. S.; Etman, A.; Siddiqi, I. N.; Cen, S.; Matcuk, G. R.; Brynes, R. K.; Salama, M. E.
Abstract: Introduction: Evaluation of cellularity is an essential component of bone marrow trephine biopsy examination. The standard practice is to report the results as visual estimates (VE). Digital image analysis (DIA) offers the promise of more objective measurements of cellularity. Methods: Adult bone marrow trephine biopsy sections were assessed for cellularity by VE. Sections were scanned using an Aperio AT2 Scanscope and analyzed using a Cytonuclear (version 1.4) algorithm onhalo software. Intraclass correlation (ICC) was used to assess relatedness between VE and DIA, and between MRI and DIA for a separate subset of patients. Trephine biopsy sections from a subset of patients with bone marrow biopsies uninvolved by malignancy were assessed for age‐related changes. Results: Interobserver VE agreement was good to excellent. The ICC value was 0.81 for VE and DIA, and 0.50 for MRI and DIA. Linearity studies showed no statistically significant trend for age‐related changes in cellularity in our cohort ( r  = −.29, P  = .06). Conclusions: Agreement was good between VE and DIA. It may be possible to use DIA or VE to measure cellularity in the appropriate clinical scenario. The limited sample size precludes similar determinations for MRI calculations. Further studies examining healthy donors are necessary before making definitive conclusions regarding age and cellularity.